Content analysis study on database technology trends in academic writing in ACM & IEEE (2007-2013) / Azizah Safie - Safie, Azizah (2014)
Data base technology trends evolve rapidly, which means not only the evolution of data type but in every part of database technology itself such as the scalability of large data size, spatial database or geodatabase, mobile database and many more. The traditional database model such hierarchical data model, network data model and relational data model are still be used in currents industry, but it may not suitable to afford large amount of data at the same time. Data model is the backbone of any database technology because of Database Management System (DBMS) is relies on it. Data model act as a construct, concept and design to a database system, where the database should follow the concept of data model. This study will adopt a conceptual content analysis approach to a qualitative data, which are online document that are sought from two online databases publications, Association for Computing Machinery (ACM) and Institute of Electrical and Electronics Engineers (IEEE) which are recognized as the largest educational and scientific computing society. This study decides on content analysis as the method to study because it is a best way to identify the trends or phenomenon in any document. The result of the study will shows the trends in academic writing in database model from 2007 until 2013 and also the factor that influence the emergence of new data model or database technology.